Pengaruh Media Interaktif Animasi Terhadap Hasil Belajar Siswa Pada Tema 4 Subtema 2 Materi Berbagai Pekerjaan Disekitarku Kelas IV SD Negeri 121248 Pematang Siantar - Anita Keren Yemima Sirait; Lisbet Sihombing; Tarida Simanjuntak (JOURNAL SAINS STUDENT RESEARCH, 2023)
The research aims to determine: The effect of animated interactive media on the learning outcomes of class IV students with theme 4 sub-theme 2 Various student jobs in class IV of SD Negeri 121248 Pematang Siantar. Researchers chose animated interactive media because this media requires students to be more active in building their knowledge by giving students the opportunity to solve a problem using images and audio. This media also emphasizes student activity in discovering the concepts being studied and educators only act as facilitators. In this research, researchers used a pre-experimental type of research using a one group pretest-posttest design. After the researcher carried out the Pretest test, the researcher then carried out an experiment using Animation Interactive Media. Furthermore, the results of data analysis on the pretest and posttest of class IV UPTD SD Negeri 121248 Pematang Siantar with a total of 30 students. Before being given the treatment, the average pretest score was 46.83, the highest score was 75 and the lowest score was 20. Meanwhile, after the treatment was carried out using Interactive Animation Media, the posttest average score was 83.13, the highest score was 100 and the lowest score was 60. So it can be concluded that there is a significant influence on improving student learning outcomes in Theme 4 Subtheme 2 material on various jobs for Class IV SD Negeri 121248 Pematang Siantar T.A 2023/2024.